Association between Online Gaming Addiction and Aggressive Behavior among Junior High School Adolescents in Soreang - Zaenal Mutaqin; Dinda Dwi; Vera Fauziah Fatah; Dian Yuniar Syanti Rahayu; Muryati Muryati; Indita Wilujeng Astiti (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2026)
Online gaming addiction and aggressive behavior among adolescents have elicited worries over potential behavioral consequences, particularly the increase in aggressive tendencies. The situation necessitates scientific inquiry, given students' increasing exposure to online media. The objective of this study is to investigate the relationship between online game addiction and aggressive conduct in junior high school students. This study employed a quantitative, cross-sectional design. A total of 104 students from one junior high school were chosen using simple random sampling. The tools utilized were the Game Addiction Scale (GAS) and the Buss-Perry Aggression Questionnaire (BPAQ). Spearman’s rank correlation test was used to assess the data. The analysis indicated that 51% of students exhibited moderate addiction to online games, 32.7% showed low levels of addiction, and 16.3% displayed strong addiction. Concerning aggressive conduct, 53.8% were classified as moderate, 32.7% as mild, and 13.5% as high. Spearman's test revealed a weak positive correlation between online game addiction and aggression (p-value = 0.008; r = 0.259), suggesting a low positive correlation rather than a “strong link,” since r falls within the weak–moderate range. Therefore, the conclusion should be statistically more precise. The results indicate that elevated levels of online game addiction correlate with heightened aggressive behavior. Consequently, parents and educational institutions must monitor students' gaming behavior and promote better digital interactions.